1993
DOI: 10.1289/ehp.9399237
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of carcinogen exposure and cancer risk in a coke plant.

Abstract: To evaluate the association between an indicator of carcinogen exposure (peripheral blood leukocyte DNA adducts of polycyclic aromatic hydrocarbons) and an early indicator of neoplastic transformation (sputum epithelial cell membrane antigens binding by monoclonal antibodies against small cell lung cancer and against nonsmall cell lung cancer), a survey of350 coke-oven workers and 100 unexposed workers was planned. This paper reports a pilot investigation on a subgroup of 23 coke-oven workers and 8 unexposed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The risk of gastric cancer and nonmalignant respiratory diseases in workers in the coke shipment department was increased. Similarly, to evaluate the association between a carcinogenic exposure indicator (IPA adducts to peripheral blood leukocyte DNA) and an early indicator of neoplastic transformation (antigens of the epithelial cell membrane of sputum cells), Assennato et al [88] recruited 350 coke oven workers and 100 unexposed workers. The results showed that smokers, people with reduced lung function, and those with morphological dysplasia of sputum cells had high levels of DNA adducts; however, no significant difference was found between the groups of coke oven workers and unexposed controls.…”
Section: Relationship Between Different Biomarkers and Vital Statusmentioning
confidence: 99%
“…The risk of gastric cancer and nonmalignant respiratory diseases in workers in the coke shipment department was increased. Similarly, to evaluate the association between a carcinogenic exposure indicator (IPA adducts to peripheral blood leukocyte DNA) and an early indicator of neoplastic transformation (antigens of the epithelial cell membrane of sputum cells), Assennato et al [88] recruited 350 coke oven workers and 100 unexposed workers. The results showed that smokers, people with reduced lung function, and those with morphological dysplasia of sputum cells had high levels of DNA adducts; however, no significant difference was found between the groups of coke oven workers and unexposed controls.…”
Section: Relationship Between Different Biomarkers and Vital Statusmentioning
confidence: 99%